(untitled) (Confluenţe Bibliologice, 2014)
Library 3.0 is a new library science philosophy, a space for interaction, innovation, inspiration, creation. Get immediate information to users, regardless of location. Use methods of spreading like: tags, semantic web, web OPAC. Librarians constantly improved how to handle easily information with.